2010
DOI: 10.1515/hmbci.2010.037
|View full text |Cite
|
Sign up to set email alerts
|

Risk of breast cancer during hormone replacement therapy: mechanisms

Abstract: Regarding estrogen replacement therapy, two main mechanisms have to be considered for it to be discussed as a potential carcinogen in the breast, and also considering the World Health Organization definition of estrogens and estrogen/progestogen combinations as "carcinogenic": (i) the proliferative/apoptotic effects on already pre-existing estrogen-sensitive cancer cells and (ii) the production of possible genotoxic estrogen metabolites. By addition of the progestogen component, as is usual in non-hysterectomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 90 publications
(95 reference statements)
0
6
0
1
Order By: Relevance
“…Some of the experimental evidence is compatible with the hypothesis that estrogen alone may accelerate the onset of clinically detectible breast cancer, while other evidence suggests that it may have the opposite effect 2426. It is also possible that different estrogens may have different effects, and at least 10 different estrogenic compounds, in varying concentrations, are present in conjugated equine estrogens 27…”
Section: Discussionmentioning
confidence: 72%
“…Some of the experimental evidence is compatible with the hypothesis that estrogen alone may accelerate the onset of clinically detectible breast cancer, while other evidence suggests that it may have the opposite effect 2426. It is also possible that different estrogens may have different effects, and at least 10 different estrogenic compounds, in varying concentrations, are present in conjugated equine estrogens 27…”
Section: Discussionmentioning
confidence: 72%
“…E+P may enhance the proliferation of benign cells and thus increase the likelihood of errors in DNA replication, and via mutation to new cancer cells 2628. However, it has not been shown that E+P directly damages DNA, leading to mutations (initiation).…”
Section: Discussionmentioning
confidence: 99%
“…X-rays), or spontaneous mutations in, cellular genes (initiation). Following initiation, on average it takes at least 5–10 years before clinical breast cancer develops (promotion) 14 15. The hypothesis, therefore, is not whether HRT initiates carcinogenesis, but whether its use accelerates the multiplication and malignant transformation of cells already initiated.…”
Section: Evaluation Of the Crmentioning
confidence: 99%
“…Under a promotional hypothesis, the underlying assumption is that HRT accelerates the multiplication of initiated cells, so that clinically evident breast cancer develops sooner than would otherwise be the case (and it is speculated that HRT may also accelerate the growth of otherwise slowly growing cancer that is already present) 18 19. Therefore estrogens, and probably progestogens as well, as known proliferative factors could possibly enhance the median tumour doubling time, assessed for the most aggressively multiplying cells to be about 50–100 days,14 15 37 and it is generally accepted that 30–35 doublings are required to attain a tumour diameter of 1 cm, which is about the smallest lesion that can be diagnosed clinically. Thus on average at least 5–10 years will have elapsed from tumour initiation in a single cell to the time of diagnosis.…”
Section: Evaluation Of the Crmentioning
confidence: 99%